2012
DOI: 10.1080/13678868.2012.669236
|View full text |Cite
|
Sign up to set email alerts
|

Through the looking glass: challenges for human resource development (HRD) post the global financial crisis – business as usual?

Abstract: An important question for human resource development (HRD) concerns how its practices may have contributed to the global financial crisis. Commentators have highlighted that HRD must take some of the blame. First, we consider whether HRD's traditional role of contributor through performance-based development interventions, may have facilitated questionable practices in organizations. Second, we reflect on whether HRD was an irrelevant spectator through being benign and impotent; rather than challenging the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 37 publications
1
50
0
3
Order By: Relevance
“…MacKenzie et al (2012) suggest that, although HR professionals are involved in managing the 'organisation's human intellectual capital' (p.354), they have been markedly missing from analysis into the origins of the global financial crisis. Similarly, criticism for the HR profession in the US raised concerns about the lack of accountability for recruiting and rewarding irresponsible chief executives and financial risk managers that directly contributed to the global recession (Morgenson and Rosner 2011).…”
Section: Reflective Practice and The Hr Professionmentioning
confidence: 99%
“…MacKenzie et al (2012) suggest that, although HR professionals are involved in managing the 'organisation's human intellectual capital' (p.354), they have been markedly missing from analysis into the origins of the global financial crisis. Similarly, criticism for the HR profession in the US raised concerns about the lack of accountability for recruiting and rewarding irresponsible chief executives and financial risk managers that directly contributed to the global recession (Morgenson and Rosner 2011).…”
Section: Reflective Practice and The Hr Professionmentioning
confidence: 99%
“…However, it is argued that a leader's work is more complex and changing than is implied by the 'simple representation' of competences (Bolden and Gosling, 2006, 160). Recently it has been suggested that an uncritical acceptance of senior leaders values which find expression in competences, was also a feature of the failure by HRM/HRD professionals to provide a counter to short-term and risky decisions that created the GFC (MacKenzie et al 2012). …”
Section: Leaders = Leadershipmentioning
confidence: 99%
“…Furthermore, Gold, Holden, Iles, Stewart and Beardwell (2009) argue that HRD in practice and theory has a major influence on the interplay of leadership, culture, and employee commitment through: (i) helping to develop current and future leaders; (ii) involvement in shaping the organizational culture; (iii) building commitment among organization members; and (iv) anticipating required managerial responses to changing conditions. Similarly, McKenzie, Garavan and Carbery (2012) observed that "the shift from operational and tactical HRD to strategic HRD has witnessed a metamorphosis for HRD practitioners increasingly becoming partners in the business tasked with aligning people, strategy, and performance rather than simply promoting learning and development " (p.354). This observation echoes Kohut and Roth's (2015) claim that "HRD practitioners and scholars need International Journal of HRD Practice, Policy and Research 2016, Vol 1 No 1: 7-20 doi: 10.22324/ijhrdppr.1.102 to enter the fray of the discussion on change management" (p.231).…”
Section: Introductionmentioning
confidence: 99%